Industrial Commodity Statistics Yearbook 2009 - United Nations (United Nations, 2014)
This publication provides statistics on the production of about 600 major industrial commodities. Data was provided for the ten-year period of 2000-2009 for approximately 200 countries and territories. The commodities have been selected on the basis of their importance in world production and trade. The Yearbook is organized in two volumes, and contains correspondence tables that allow the user to link the information provided to other internationally-used product classifications.